Kinesiology tape or compression sleeve applied to the thigh does not improve balance or muscle activation before or following fatigue - Cavanaugh, M. T.; Quigley, P. J.; Hodgson, D. D.; Reid, J. C.; Behm, D. G. (The Journal of Strength and Conditioning Research, 2016)
Compression sleeves (CS) and kinesiology tape (KT) are purported to enhance proprioception, however, there is substantial conflict in the literature. Because the beneficial effects of CS and KT are more evident in the literature with recovery, the objective of this study was to examine the effects of CS and KT on balance under acute nonfatigued and postfatigued conditions. Using a within-subject, repeated-measures design, 12 university participants (5 females and 7 males) performed in a random order CS, KT, and Control conditions. Two trials of each test were conducted before the application of CS or KT (pretest 1), immediately after the application (pretest 2), with posttests at 1 and 10 minutes after 4 sets of unilateral Bulgarian squats to failure (1 minute rest between sets). Tests included a Y balance test (measures: distance reached by nondominant foot in anterior, posterior lateral, and posterior medial directions) and drop jump landing balance test from a 50-cm platform (measures: ground reaction force, electromyography, and center of pressure). The fatigue protocol induced 25.3% decrease in unilateral squat repetitions from set 1 to set 4. There were no significant condition main effects or interactions for any balance measure or EMG before or after fatigue. In conclusion, independent of fatigue, there was no significant effect of CS or KT on balance outcomes immediately and up to 10 minutes following the fatiguing intervention. Thus, nonfatigued or muscles weakened by fatigue did not benefit from CS and KT application.